Energy balance and gastrointestinal cancer - Berger, Nathan A.; Markowitz, Sanford D. (Energy Balance and Cancer, 2012)
The gastrointestinal track provides one of the distinct systems where multiple malignancies, including adenocarcinoma of the pancreas, esophagus and colon are each associated with obesity. This unique association is covered in this volume of Energy Balance and Cancer from the epidemiologic, biologic and potential etiologic viewpoint. The focus on possible dietary contribution as well as the role of exercise in prevention and therapy is presented in both animal model and patient based studies. Special focus is provided also on the role of genetic mutations and inflammatory pathways as drivers of these obesity related gastrointestinal malignancies. Overall, this volume on Energy Balance and Gastrointestinal Malignancies should be valuable to Epidemiologists, Gastroenterologists and Oncologists, as well as to students and researchers from multiple disciplines interested in understanding and disrupting the association between obesity and cancer.